The protective effect of cilostazol on transverse rectus abdominis myocutaneous flap in rats - Ozdemir, Ayfer; Orhan, Erkan; Altun, Serdar; Inozu, Emre (Medical Journal Sweden Ab, 2017)
Objective: Transverse Rectus Abdominis Myocutaneous (TRAM) flap is commonly used in breast reconstruction. The aim of this study is to demonstrate the effects of cilostazol on TRAM flap viability in a rat TRAM model. Methods: Twenty-four Wistar rats were used. They were divided into four groups. Rats in Group 1 were applied TRAM flap. In Group 2, cilostazol 30 mg/kg was administered to rats via oral gavage 3 hours before the flap surgery. After the flap surgery, cilostazol 30mg/kg was administered via oral gavage twice a day for 7 days. In Group 3 before the flap surgery, cilostazol 30 mg/kg was administered via oral gavage twice a day for 7 days, and treatment continued for 7 more days after the flap surgery. In Group 4 before the flap surgery, cilostazol 30 mg/kg was administered via oral gavage twice a day for 7 days and treatment was discontinued after the flap surgery. Result: The mean necrosis rate in Group 1 was 41.69%, in Group 2 it was 27.0%, in Group 3 it was 6.66%, and in Group 4 it was 11.2%. The necrosis rate in Group 1 was found to be statistically significantly higher than other groups (p < .01), the necrosis rate in Group 2 was found to be statistically significant higher than Groups 3 and 4 (p < .01), and the necrosis rate in Group 4 was found to be statistically significant higher than Group 3 (p < .01). Conclusion: Cilostazol treatment seemed to increase the viability of TRAM flap, especially when administered as adjuvant therapy.
Keywords: TRAM flap; cilostazol; flap viability